Frailty after lung transplantation is associated with impaired health-related quality of life and mortality. Issue 8 (6th May 2020) - Venado, Aida; Kolaitis, Nicholas A; Huang, Chiung-Yu; Gao, Ying; Glidden, David V; Soong, Allison; Sutter, Nicole; Katz, Patricia P; Greenland, John R; Calabrese, Daniel R; Hays, Steven R; Golden, Jeffrey A; et al.
Abstract : Background: Lung transplantation and related medications are associated with pathobiological changes that can induce frailty, a state of decreased physiological reserve. Causes of persistent or emergent frailty after lung transplantation, and whether such transplant-related frailty is associated with key outcomes, are unknown. Methods: Frailty and health-related quality of life (HRQL) were prospectively measured repeatedly for up to 3 years after lung transplantation. Frailty, quantified by the Short Physical Performance Battery (SPPB), was tested as a time-dependent binary and continuous predictor. The association of transplant-related frailty with HRQL and mortality was evaluated using mixed effects and Cox regression models, respectively, adjusting for age, sex, ethnicity, diagnosis, and for body mass index and lung function as time-dependent covariates. We tested the association between measures of body composition, malnutrition, renal dysfunction and immunosuppressants on the development of frailty using mixed effects models with time-dependent predictors and lagged frailty outcomes. Results: Among 259 adults (56% male; mean age 55.9±12.3 years), transplant-related frailty was associated with lower HRQL. Frailty was also associated with a 2.5-fold higher mortality risk (HR 2.51; 95% CI 1.21 to 5.23). Further, each 1-point worsening in SPPB was associated, on average, with a 13% higher mortality risk (HR 1.13; 95% CI 1.04 to 1.23). Secondarily, we found that sarcopenia, underweight and obesity, malnutrition, and renal dysfunction were associated with the development of frailty after transplant. Conclusions: Transplant-related frailty is associated with lower HRQL and higher mortality in lung recipients. Abnormal body composition, malnutrition and renal dysfunction may contribute to the development of frailty after transplant. Confirming the role of these potential contributors and developing interventions to mitigate frailty may improve lung transplant success.